Cinematography as an educational and cultural resource: the case of historical cinema - Guevara Flores, Ernesto (2016)
The article explores the possibilities of the cinema as a teaching resource for school and undergraduate education, based on the contributions of communicators and educators, who have linked cinematography and education. In that regard, the specific case of historical cinema and its potential is taken, considering its informative, motivational and epistemological functions in the educational and cultural domain, thus proposing a method to use cinema in classrooms.